2019
DOI: 10.1121/1.5102039
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the production of prosodic boundaries in American English

Abstract: This study investigates individual differences in the weighting of phonetic properties in the production of prosodic boundaries in American English. The motivation of the study is to inform understanding of individual speaker variation and its accommodation in the representation of prosodic structure. In an acoustic study, 32 speakers produced 16 sentence pairs differing in type of boundary (Intonational Phrase (IP) boundary vs. Word boundary). Pause duration, phrase-final lengthening (three syllables before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…These findings not only support the existence of variation in the use of phonetic cues to mark focus, they also indicate that some strategies are communicatively more successful than the others. Finally, the variable use of phonetic cues has also been reported in British and American English (Kim 2019;Ouyang and Kaiser 2015;Peppé et al 2000) as well as in German (Baumann et al 2006;Cangemi et al 2015). The presence of individual variation reported in these languages shows that this phenomenon is not specific to Urdu or Hindi.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…These findings not only support the existence of variation in the use of phonetic cues to mark focus, they also indicate that some strategies are communicatively more successful than the others. Finally, the variable use of phonetic cues has also been reported in British and American English (Kim 2019;Ouyang and Kaiser 2015;Peppé et al 2000) as well as in German (Baumann et al 2006;Cangemi et al 2015). The presence of individual variation reported in these languages shows that this phenomenon is not specific to Urdu or Hindi.…”
Section: Discussionmentioning
confidence: 89%
“…This is further supported by the differences found in the perception of prosodic phrasing structure in the online survey. The existence of speaker related variation in the use and manipulation of phonetic cues has also been reported in Hindi (Kügler 2020), Tamil (Keane 2014), German (Baumann et al 2006;Cangemi et al 2015;Schuppler and Ludusan 2020), American English (Kim 2019;Ouyang and Kaiser 2015), British English (Peppé et al 2000), Russian (Luchkina and Cole 2019), as well as New Zealand English and Samoan (Calhoun et al 2019). These are typologically different languages with distinct intonation systems.…”
Section: Variation In Prosodic Phrasingmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, Ouyang and Kaiser (2015) observed that American English-speaking individuals differed in how strongly they encode informativity (i.e., focus type, contextual probability, and word frequency) via the F0 contour, in that some speakers made larger differences in terms of F0 excursion between the levels of these three variables. Kim (2019) found considerable individual differences in prosodic cues to phrase boundaries in American English speakers. While all speakers produced pauses at IP boundaries, they differed in pause durations.…”
Section: Speaker-specific Variability (The Individual Perspective)mentioning
confidence: 90%
“…The authors suggest an individual-specific network of phonological knowledge that leads to speaker- and listener-specific differences in the identification of prosodic contrasts. When it comes to online processing of prosody, Kim (2019) observed differences in prosodic cue usage for the perception of disambiguating boundaries over the course of listeners’ fixations to the target picture in a visual world paradigm: some listeners looked to the correct target earlier than others, depending on the available prosodic cues, which varied between conditions.…”
Section: Introductionmentioning
confidence: 99%